Optimum treatment for mediastinal lymph node positive (N2) resectable non-small cell lung cancer: what is the role for surgery?. Issue 11 (1st November 2016) - Awan, Musaddiq; Sharma, Neelesh; Towe, Christopher W.; Efird, Jimmy T.; Machtay, Mitchell; Biswas, Tithi
ABSTRACT: Introduction : A third of patients with Non-Small Cell Lung Cancer (NSCLC) present with Stage III disease with mediastinal (N2) nodal involvement representing an extremely heterogeneous population with a generally poor prognosis. Areas covered : This article describes the complexity of Stage III-N2 patients reviewing the outcomes of key clinical trials while highlighting the trial designs and subtleties that have created controversy in management. Both bimodality approaches combining chemotherapy with either surgery or radiation and trimodality approaches combining chemotherapy with both local therapies are reviewed. Finally, prognostic factors and future directions are explored for the management of this population. Expert commentary : Upfront surgery is not recommended for patients with Stage III-N2 NSCLC. Neoadjuvant approaches with both chemotherapy and chemoradiation are acceptable in a multidisciplinary setting if appropriate surgery is performed by a dedicated thoracic surgeon. Non-operative candidates should receive definitive concurrent chemoradiation. Innovative approaches are necessary to improve outcomes in this population.